2002
DOI: 10.1080/1061186021000038346
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targeting to the Brain: Transfer of Picolinic Acid Along the Olfactory Pathways

Abstract: Picolinic acid (PA) protects against quinolinic acid- and kainic acid-induced neurotoxicity in the brain. To study the uptake of PA to the brain, we administered [3H]PA via a unilateral nasal instillation or iv injection to mice. Autoradiography demonstrated a rapid uptake of radioactivity in the olfactory nerve layer and in the ipsilateral olfactory bulb (OB) following nasal instillation of [3H]PA. After 4 h, there was a high level of radioactivity in the central parts of the ipsilateral OB and olfactory pedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This connection may therefore be a portal of entry of drugs and toxicants into the brain, thus circumventing the blood-brain barrier. A significant uptake of some drugs and chemicals has been reported in the ipsilateral olfactory bulb after a unilateral intranasal instillation (Dahlin et al 2000;Bergstrom et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This connection may therefore be a portal of entry of drugs and toxicants into the brain, thus circumventing the blood-brain barrier. A significant uptake of some drugs and chemicals has been reported in the ipsilateral olfactory bulb after a unilateral intranasal instillation (Dahlin et al 2000;Bergstrom et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Bergstrom et al [95] have also reported the transport of picolinic acid along the olfactory pathways after administration via intranasal and intravenous routes in mice. Autoradiography demonstrated rapid uptake of radioactivity in the olfactory nerve layer and in the ipsolateral olfactory bulb following intranasal administration.…”
Section: Delivery Of Non-peptide Molecules To the Cnsmentioning
confidence: 94%
“…Since the olfactory bulb is not protected by the blood-brain barrier (Oberdorster et al 2004), this brain region is continuously exposed to airborne pollutants (Franco et al 2007). Airborne environmental contaminants as well as pharmaceuticals locally administrated on the nasal mucus may be directly transferred to the olfactory bulb along the axons of the olfactory neurons, as their dendrites project into the nasal mucus and their axons into the olfactory bulb (Bergstrom et al 2002;Eriksson et al 1999). Pathological alterations induced by airborne environmental toxicants may contribute to the initiation of protein aggregation in the olfactory bulb, which in turn triggers the spread of the pathology within the brain (Attems et al 2014).…”
Section: Introductionmentioning
confidence: 99%